Design and fabrication of floor cleaning device / Ahmad Aiman Roslan - Roslan, Ahmad Aiman (2024)
Recently, many people facing a problem relate to cleanliness especially people who work in commercial industry and food service industry. Every place needs to have a cleaning tool at their place to make sure the cleanliness at their place maintained. The current cleaning method may not provide the best cleaning results and time-consuming. During closing hour, it will take time to make sure the floor is clean, and it use a lot of energy. The objective of this project is to design a floor cleaning device using solidwork software and to fabricate a floor cleaning device to reduce physical strength. As a result, the floor cleaning device with ergonomic design, high durability material, costefficiency and user-friendly will be produce. Hopefully, from this project may help the worker in the commercial industry and food service industry to reduce time consuming for cleaning process, minimize the physical injury during the process and can reduce cost effectively.